PENGARUH VARIASI KONSENTRASI BAHAN ADITIF LARUTAN NANOPARTIKEL PERAK TERHADAP SIFAT ANTI-JAMUR CAT DINDING SEBAGAI APLIKASI TEKNOLOGI NANO DALAM INDUSTRI CAT DINDING - Dwandaru, W.S. Brams; Putri, Z.M. Chrishar; Yulianti, E. (Universitas Negeri Yogyakarta, 2016)
This research aims to (1) identify the characteristics of silver nanoparticle by using UV-Vis spectrophotometer; (2) determine the anti-fungus property of wallpaint after being added by silver nanoparticle solution; and (3) determine the effect of silver nanoparticle solution concentration towards the anti-fungus property of the wallpaint. This study begins by synthesizing the silver nanoparticle solution with concentrations of (in mM) 1, 2, 3, 4, and 5. Then as much as 80% and 20% of wall paint and silver nanoparticle solution, respectively, are mixed. The solution obtained is tested using UV-Vis pectrophotometer and followed by conducting an experiment of the anti-fungus properties of the wallpaint with silver nanoparticle solution as an additive material. The measurements are conducted three times. This research shows that concentration of the silver nanoparticle solution affects the anti-fungus properties of the wallpaint. The diameter of the anti-fungus for the concentration of (in mM) 1, 2, 3, 4, and 5 are (in cm) 1.36; 1.42; 1.45; 1.53; and 1.79, respectively. The greater the concentration, the greater the diameter of the anti-fungus. Therefore, the silver nanoparticle solution can be used to obstruct the fungus growth on the wall